2021
DOI: 10.1093/bioadv/vbab020
|View full text |Cite
|
Sign up to set email alerts
|

RibDif: can individual species be differentiated by 16S sequencing?

Abstract: Metataxonomic analysis is now routinely used to profile the microbiome of virtually every ecological niche on planet Earth. The use of Amplicon Sequence Variants (ASVs), proposing to be the exact biological 16S rRNA amplicon sequences of a given biological system, is now considered the gold standard. However, the 16S rRNA genes, and in particular the amplicons derived from it, are not unique for most species nor are they necessarily unique within individual genomes. Despite these restrictions, individual ASVs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 9 publications
1
37
0
Order By: Relevance
“…Dereplication and inference were performed using the DADA2 pipeline. After merging the paired reads and chimera filtering, an ASV table was constructed (to resolve bacteria at the species level [ 25 ]). The ASVs were taxonomically assigned based on the SILVA 16S rRNA gene database (version 132) [ 26 ] using a naive Bayesian classifier method [ 27 ] implemented in DADA2.…”
Section: Methodsmentioning
confidence: 99%
“…Dereplication and inference were performed using the DADA2 pipeline. After merging the paired reads and chimera filtering, an ASV table was constructed (to resolve bacteria at the species level [ 25 ]). The ASVs were taxonomically assigned based on the SILVA 16S rRNA gene database (version 132) [ 26 ] using a naive Bayesian classifier method [ 27 ] implemented in DADA2.…”
Section: Methodsmentioning
confidence: 99%
“…We compared taxonomic profiles of phyla, class, family and genus between shotgun metagenomics and 16S rRNA and ITS amplicon sequencing. It has been reported that for ~42% of bacterial genera there will be pairs of congeneric sequences that cannot be easily separated because of the high similarity of their 16S rRNA sequences (Vetrovsky and Baldrian, 2013 ; Strube, 2021 ). Hence, since species and strains are particularly challenging to identify (or unattainable) for the metataxonomic methods used here (Vetrovsky and Baldrian, 2013 ), and are not commonly reported in vermicomposting (e.g., Gopal et al, 2017 ; Dominguez et al, 2019 ), we did not consider lower-than-genus taxonomic levels in our analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the internal transcribed spacer (ITS) region of the rRNA operon for fungi (Nilsson et al, 2019a ) is an effective DNA barcode (Schoch et al, 2012 ) to characterize fungal diversity also due to an extensive database of reference sequences (Merget et al, 2012 ; Santamaria et al, 2018 ; Nilsson et al, 2019b ). However, despite their widespread use in microbial diversity studies, these two target genes are not as effective at classifying sequences at the species and strain levels (Vetrovsky et al, 2016 ; Johnson et al, 2019 ; Strube, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The number of unique copies of the marker gene for each strain and the percent sequence identity among them will inform the expected number of taxa after mock community sequencing. This is especially important when operational taxonomic units (OTUs) are based on 100% sequence identity (e.g., using the amplicon sequence variant (ASV), zOTU, or ESV definitions at 100%; Starke, Pylro, & Morais, 2020; Strube, 2021), as each unique copy of a marker gene will become a distinct taxonomic unit, including any propagated PCR errors. The gene copy numbers for many cultivable strains or close relatives are available in sequenced genomes in the National Center for Biotechnology Information (NCBI) database or, in the case of the 16S rRNA gene, in the rrnDB (https://rrndb.umms.med.umich.edu/; Stoddard et al., 2015).…”
Section: Strategic Planningmentioning
confidence: 99%